1992
DOI: 10.1080/03079459208418830
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillosis in ostriches

Abstract: SUMMARYA severe case of aspergillosis was observed in a flock of 3-to 8-week-old ostriches at a farm in Israel. A. niger and A. flavus were isolated from the lungs of affected ostriches. A heavy contamination with both fungi was detected in the hatchery, suggesting a brooder borne infection. The clinical and pathological findings observed in this case are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 2 publications
1
49
0
2
Order By: Relevance
“…Sporangia and sporangiospores sometimes develop in vivo. Thick zygospore-like structures have also been observed in invaded tissues, although a true zygospore formation has not been found in vivo (Baker, 1971;Rippon, 1974;Emmons et al, 1977;Koheler et al, 1978;Chandler et al, 1980;Scholer et al, 1983;Kuttin, 1992). Similar morphological characteristics may be seen in infected tissues of aquatic and terrestrial animals with some oomycetes like Saproleqnia and Pythium sp.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Sporangia and sporangiospores sometimes develop in vivo. Thick zygospore-like structures have also been observed in invaded tissues, although a true zygospore formation has not been found in vivo (Baker, 1971;Rippon, 1974;Emmons et al, 1977;Koheler et al, 1978;Chandler et al, 1980;Scholer et al, 1983;Kuttin, 1992). Similar morphological characteristics may be seen in infected tissues of aquatic and terrestrial animals with some oomycetes like Saproleqnia and Pythium sp.…”
Section: Discussionmentioning
confidence: 50%
“…Aspergillosis and candidosis have been reported in wild and domestic birds including ostriches (Archibald, 1913;Jowett, 1913;Ainsworth & Austwick, 1973;Campbell, 1986;Chute & Richard, 1991;Fuchs, et al, 1991;Perelman, 1991;Perelman & Kuttin, 1992). Zygomycosis occurs more seldom in birds (Loupal, 1981;Fuchs et al, 1991) and has not previously been reported in ostriches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the kori and houbara bustard chicks that died of aspergillosis were reared together. Poor hatchery and brooder sanitation are reported to be important sources of infection in ostrich chicks ( Perelman et al, 1992). Predisposing factors to aspergillosis include immunosuppression, malnutrition and unhygienic environmental conditions (Cooper, 1978, Redig, 1980, Campbell, 1986and Jordan, 1990).…”
Section: Discusslonmentioning
confidence: 99%